Call for developing indigenous organisational theories in India: setting agenda for future. (11th July 2007) - Panda, Abinash; Gupta, Rajen K.
If we accept Virmani's (2005) argument that management in the organisations in India is somehow effected, by implication, we also agree that we have not understood how organisations in India are managed effectively. It calls for developing indigenous concepts in the organisational domain, which requires moving away from unimaginative replicative studies using quantitative methods towards carrying out contextually relevant studies using appropriate methods. On the basis of meta-review of organisational research (particularly in the area of organisational behaviour) in the past several decades, this paper analyses the reason why theory-building researches are not thriving in India to a desired extent and suggests some ways out of it. Academic scholars, academic institutions and corporate world can play significant and meaningful roles in creating a new breed of researchers focusing on exploring the indigenous understanding of organisations in India and management thereof. We have delineated their roles from that perspective. This paper also discusses about the possibilities of upgrading the quality of research in India, and the theoretical, methodological and situational challenges that researchers in India face while conducting organisationally relevant indigenous researches.